The 4STMD Method for a Contextual Colloid Module on Tofu Waste Coagulation - Abdurachman, Bagas; Anwar, Sjaeful; Rohman, Ijang (Universitas Negeri Medan, 2025)
The abstract nature of chemistry often leads to low student comprehension, a problem exacerbated by a lack of teaching materials that connect concepts to real-world situations. This research aimed to develop a valid, practical, and effective contextual teaching module on the colloid system using Four Steps Teaching Material Development (4STMD) method. The research following the stages of Design, Development, and Evaluation (DDE). The module's unique context is the application of colloid chemistry principles to the treatment of tofu liquid wastewater using Moringa oleifera seeds as a natural coagulant. The development process followed the four stages of 4STMD: Selection, Structuring, Characterization, and Didactic Reduction. The module's quality was evaluated by three expert chemistry teachers and tested for understandability with 63 high school students. The results of the expert validation indicated that the module is Very Feasible, with high scores in content (95.2%), language (85.7%), presentation (93.7%), and graphical feasibility (85.3%). Furthermore, the student understandability test yielded an average score of 93.33%, categorizing the module as